Determinan Perilaku Pencegahan COVID-19 Pasca Pandemi pada Pengunjung Rumah Sakit “X” di Jakarta tahun 2023 - Soepadji, Mariyono; Nugraha, Susiana; Sulistyowati, Yeny (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2023)
Hospital visitors are at high risk of being exposed to and infected by infectious diseases. Data on visitors to Hospital